Investigation of charges-driven interactions between graphene and different SiO2 surfaces. (July 2019) - Pantano, Maria F.; Iacob, Erica; Picciotto, Antonino; Margesin, Benno; Centeno, Alba; Zurutuza, Amaia; Galiotis, Costas; Pugno, Nicola M.; Speranza, Giorgio
Abstract: As being only one atom thick, most of the device applications require graphene to be partially or fully supported by a substrate, which is typically silicon dioxide (SiO2 ). According to a common understanding, graphene interacts with SiO2 through weak, long-range van der Waals forces, emerging between instantaneous/induced dipoles, in contrast to the experimental evidence that reveals a surprisingly high interaction between graphene and SiO2 . In order to get further insight into this phenomenon, we carried out diverse physical measurements on SiO2 substrates, prepared via different fabrication protocols, with and without graphene on top. As a result, the role of the oxide surface charges is recognized for the first time as a main factor causing graphene to strongly interact with SiO2 . Our findings provide guidelines for designing 2D materials interaction with a substrate through modulation of surface charges. This, in turn, can facilitate the development of new graphene based microelectronic devices. Graphical abstract: Image 1